(untitled) (Global Journal of Management and Business Research, 2018)
Mustafa (pbuh) Science and Technology Foundation (MSTF) has started its activities within a specifically developed framework to honor the scientists of the Islamic world and appreciate their efforts, along with training future scientists worldwide. The MSTF tries to develop cooperation, synergy, and convergence in the realm of modern sciences and new technologies and also puts effort into making the distinguished figures in science and technology role models. It makes a consolidated effort to improve the general welfare of people worldwide by benefiting from values such as reverence for divine religions, respect and humanity. This venerable Foundation provides values of dignity, trust, a supportstructure for the development of science and technology, an educational enterprise for uncovering the truth, assuming social responsibility, and laying down the groundwork for construction of a grand new and contemporary Islamic civilization. This study is an introduction of Mustafa Prize and its Objectives, Salient Features, Services and an effective transfer of the same. Additionally, it looks at the role which can be played to enlarge and enrich Science and technology among Moslem Countries.